Gender differences in gang participation, delinquency, and substance use - Bjerregaard, Beth (Journal of quantitative criminology, 1993)
The purpose of this paper is to respond to gaps in our knowledge about patterns of female gang participation and its causes and consequences. Data from the Rochester Youth Development Study, a panel study that overrepresents adolescents at high risk for delinquency, are used to compare gang participation and delinquent involvement of female and male adolescents. We then examine the role of theoretical variables associated with both female and male gang membership. The results lead us to conclude that, for females as well as males, involvement in gangs is associated with substantially increased levels of delinquency and substance use. There is also some similarity in the factors associated with gang membership for both sexes, although lack of school success emerges as a factor of particular salience for female adolescents. The results suggest that theory and intervention need to address the phenomenon of female gang membership as an important component of urban youth problems.